2016
DOI: 10.3390/beverages2030023
|View full text |Cite
|
Sign up to set email alerts
|

The Physicochemical Optimization and Acceptability of a Cashew Nut-Based Beverage Varying in Mango Juice and Sugar: A Pilot Study

Abstract: The development of a lactose-free beverage comes as a new feeding alternative to a product with excellent nutritional and functional characteristics to individuals with food restrictions related to milk. Thus, this study aimed to develop a cashew nut beverage with added mango juice and prebiotic substances by means of evaluating its sensory characteristics and physicochemical optimization. A 2 2 central composite rotatable design with five repetitions at the central point was applied to evaluate the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
(25 reference statements)
1
3
0
2
Order By: Relevance
“…The increment in TSS content might be due to the contribution of soluble solids by the addition of ascorbic acid and lemon juice. A similar increment in TSS was also reported in a previous study on cashew nut ameliorated in mango juice [17] and microgreen and fruit-based RTS beverages [18].…”
Section: Effect On Tsssupporting
confidence: 88%
“…The increment in TSS content might be due to the contribution of soluble solids by the addition of ascorbic acid and lemon juice. A similar increment in TSS was also reported in a previous study on cashew nut ameliorated in mango juice [17] and microgreen and fruit-based RTS beverages [18].…”
Section: Effect On Tsssupporting
confidence: 88%
“…O aroma da castanha de caju, apesar de ser familiar ao consumidor, atualmente não é encontrado em bebidas à venda no Brasil, o que pode influenciar os consumidores a uma maior aceitação de formulações que possuem um aroma mais característico de maracujá. Rebouças et al (2016) verificaram que o teor de sólidos solúveis pode influenciar a textura, a doçura e o sabor dos alimentos. As bebidas com menor teor de sólidos solúveis, sua aceitação sensorial foi mais baixa; já quando a concentração de sólidos foi maior, a aceitação global da bebida também aumentou.…”
Section: Análise Sensorialunclassified
“…Milk obtained from brazil nuts (Cardarelli & Oliveira, 2000;Felberg et al, 2004Felberg et al, , 2009, almond nuts (Bernat et al, 2014) and babassu (Carneiro et al, 2014) have been reported. Prebiotic beverages made from cashew nut kernels, passion fruit juice and mango juice have also been reported (Rebouças et al, 2014(Rebouças et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%